Identification of factors associated with non-adherence to recommended COVID-19 preventive behaviours: a cross-sectional study based on a survey among 1004 French primary care professionals - Cédric Rat; Aurélie Gaultier; Céline Bouton; Pauline Meziere; Julie Dupouy (BMJ Open, 2023)
Objectives Since the beginning of the COVID-19 pandemic, adherence to preventive behaviours to limit virus spread has been a major issue. The study objective was to identify factors associated with non-adherence to preventive behaviours among general practitioners (GPs) during the COVID-19 pandemic using data from a questionnaire completed during the French National Congress of General Medicine in June 2021.Design This descriptive study relied on data collected with a questionnaire during the national congress on general medicine in Bordeaux, France, from 16–18 June 2021.Setting The study was conducted in primary care in France.Participants Out of a total of 1004 GPs and GP trainees, 755 completed the questionnaire during conferences and 249 were contacted by mail.Results The questionnaire included questions on sociodemographic characteristics and COVID-19 related preventive behaviours, beliefs and experiences. Answers to questions that explored the Health Belief Model components were selected and then compared among participants who reported appropriate preventive behaviours (wearing face masks and social distancing) and participants who reported non-adherence. Analysis was based on multivariate logistic regression.The responders’ mean age was 35.8 years; 61.64% were women, 61.9% were practising GPs and 37.2% were GP trainees. Moreover, 96.6% of participants had completed the COVID-19 vaccination schedule. Non-adherence (reported by 72/1004 participants) was more frequent among smokers (OR=2.57, 95% CI 1.29 to 4.83, p=0.005) and younger participants (OR=0.95, 95% CI 0.92 to 0.98, p=0.005). Complete COVID-19 vaccination or a previous infection was not associated with non-adherence and has been poorly described.Conclusion More studies are needed to confirm the factors involved in the adoption of COVID-19 preventive behaviours by healthcare professionals and to explore the beliefs and barriers to the adoption of these behaviours.